2018
DOI: 10.1097/j.pain.0000000000001406
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional properties distinguish the substance P and gastrin-releasing peptide subsets of excitatory interneuron in the spinal cord dorsal horn

Abstract: Excitatory interneurons account for the majority of neurons in the superficial dorsal horn, but despite their presumed contribution to pain and itch, there is still limited information about their organisation and function. We recently identified two populations of excitatory interneuron defined by expression of gastrin-releasing peptide (GRP) or substance P (SP). Here we demonstrate that these cells show major differences in their morphological, electrophysiological and pharmacological properties. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(148 citation statements)
references
References 75 publications
(161 reference statements)
10
136
1
1
Order By: Relevance
“…The mouse monoclonal antibody NeuN, which was generated against cell nuclei extracted from mouse brain, was found to react with a protein specific to neurons (Mullen, Buck, & Smith, ), and this has subsequently been identified as the splicing factor Fox‐3 (Kim, Adelstein, & Kawamoto, ). We have found that the guinea‐pig NeuN antibody stains the same cells as the mouse antibody (Dickie et al, ). Staining with the neurotensin antibody is identical to that seen with a well‐characterized rabbit neurotensin antibody, and is blocked by preincubation with 10 −4 M neurotensin (Porteous et al, ).…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…The mouse monoclonal antibody NeuN, which was generated against cell nuclei extracted from mouse brain, was found to react with a protein specific to neurons (Mullen, Buck, & Smith, ), and this has subsequently been identified as the splicing factor Fox‐3 (Kim, Adelstein, & Kawamoto, ). We have found that the guinea‐pig NeuN antibody stains the same cells as the mouse antibody (Dickie et al, ). Staining with the neurotensin antibody is identical to that seen with a well‐characterized rabbit neurotensin antibody, and is blocked by preincubation with 10 −4 M neurotensin (Porteous et al, ).…”
Section: Methodsmentioning
confidence: 79%
“…Häring et al did not define a population specifically associated with GRP expression, and they reported that GRP mRNA was present in cells belonging to several of their populations (Glut5‐12). Although virtually all eGFP‐expressing cells in the GRP‐eGFP mouse contain GRP mRNA, many cells with GRP mRNA do not express GFP in this line (Dickie et al, ; Solorzano et al, ), and this suggests that eGFP is restricted to a subset of the GRP‐expressing cells. We have found that at least some of these GRP‐eGFP cells contain mRNA for the neuromedin U receptor 2 (Nmur2; AMB, unpublished data), and these may therefore correspond to the Glut8 population, in which Nmur2 mRNA is enriched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests that in neurons expressing gastrin‐releasing peptide, the single‐spiking phenotype is seen in a third of cells (Dickie et al. ); it is possible that neurons expressing this peptide more sparse or absent in the TNc.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our data indicate that single-spiking neurons are much less frequent in the mouse TNc at age p14-35 and recorded at 28°C than in the dorsal horn preparation. Recent work suggests that in neurons expressing gastrin-releasing peptide, the single-spiking phenotype is seen in a third of cells (Dickie et al 2019); it is possible that neurons expressing this peptide more sparse or absent in the TNc.…”
Section: Tonic Phasic and Delayed Cellsmentioning
confidence: 99%